The Use of Mesh Plates for Difficult Fractures of the Patella - Volgas, David; Dreger, Tina K. (The Journal of Knee Surgery, 2017)
Patella fractures present some of the more complicated fracture patterns in orthopaedic trauma care. This is partially due to the small size of the fragments but also the articular nature of each fragment. Fixation methods such as cerclage wiring, excision of smaller fragments, and screw fixation of larger fragments all have their own challenges. Our study examined our Level I trauma center's experience with variable angle locked 2.7 mm titanium plates for treatment of comminuted patella fractures or treatment of patellar nonunion. After Institutional Review Board approval, we used billing records to identify 105 patients who had undergone operative management of a displaced patella fracture between January 2011 and December 2015. We reviewed the radiographs of these patients to identify which patients underwent treatment with a mesh plate. We found 16 patients (6 males and 10 females) who had undergone fixation with a mesh plate; mean age was 47 years. Nine patients underwent primary open reduction internal fixation (ORIF) and seven underwent mesh plate fixation for failed ORIF of a patella fracture. The mean visual analog pain score was 2.75 (range, 0–9). The mean range of motion was 1 degree of extension (range, 0–10 degrees) to 110 degrees of flexion (range, 45–135 degrees). All fractures healed. Five patients required hardware removal for pain. This review illustrates the effectiveness of the locking mesh plate in two challenging clinical scenarios: that of patellar nonunion and comminuted fractures that preclude standard fixation methods. Although multiple options exist for patellar fracture fixation, the titanium mesh locking plate can be an effective option for retaining the patella in the setting of comminution. Further comparative studies should be undertaken to determine which method of treatment may be superior in the treatment of these fractures.
Keywords: patellar fractures; patellar nonunion; osteoporosis; fixation; mesh locking plate